ANALISIS PEMBIAYAAN MUSYARAKAH PADA PENDAPATAN USAHA KECIL SEBELUM DAN SESUDAH PEMBIAYAAN MUSYARAKAH DI PT BPRS HIKMAH WAKILAH (KANTOR PUSAT) - Azlina; Mirnawati; Lisnawati; Khairita H (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2023)
This research aims to determine the influence of Musyarakah financing on the increase of income for small businesses at PT BPRS Hikmah Wakilah Kantor Pusat. The data collection technique was conducted by gathering secondary data in the form of documents containing customer income from Musyarakah financing before and after the financing was provided. Out of a population of 391, the sample size was determined using the Slovin formula, resulting in 98 samples, and the sample was drawn using the simple random sampling technique. Data analysis techniques were carried out through descriptive statistics, normality tests, and hypothesis tests using SPSS 26.0. From the descriptive statistical results, it was found that the average income after financing was higher than before financing. The normality test using the Kolmogorov-Smirnov test showed that the data was not normally distributed, leading to the use of the nonparametric Wilcoxon Sign rank test for data comparison. The results of the Wilcoxon Sign rank test, an Asymp. A Sig (2-tailed) value of 0.000 was obtained, which is less than the critical limit of the research at 0.05. Thus, the research accepts the alternative hypothesis (Ha) and rejectsthe null hypothesis (Ho), indicating that there is a significant difference in income between before and after financing, and all samples experienced an increase in income after the financing or had a positive value.